PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA KARAKTER PESERTA DIDIK DI KELAS VIII MTS HIDAYATUL MUBTADIIN - Sucya Imaningsih (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
The purpose of this study was to analyze the role of PAI teachers in fostering the character of students in class VIII of MTs Hidayatul Mubtadiin Islamic Junior High School. This research is a qualitative research with descriptive research methods. Data collection techniques with observation, interview and documentation techniques. The analytical techniques used are data reduction, data presentation and data verification which is carried out based on the research focus taken. Data validity tests are carried out by extending observations, increasing persistence, triangulation, analyzing negative cases, using reference materials and conducting memberchecks. The validity test of the data is carried out to prove that the data received is the data that is actually contained in the research site. The results of the analysis showed that the character building of students in class VIII of MTs Hidayatul Mubtadiin Islamic, PAI teachers was greatly helped by the SOPs made by the school, including: first, namely the nine aspects of the school's flagship curriculum in class VIII of MTs Hidayatul Mubtadiin applied in subjects, Code of Conduc in class VIII of MTs Hidayatul Mubtadiin Islamic which is a code or trait that contains the personality that must be possessed by school students in class VIII of MTs Hidayatul Mubtadiin Islamic, the third EA (Excel Apreciation), which is a point that is given to students and is a consequence of the actions of students who violate school rules by deducting points every time they violate. From some of the things above, PAI teachers will be very easy to cultivate the character of students to become individuals with character and achieve the expected goals and results